2021
DOI: 10.22363/2312-797x-2021-16-1-54-65
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth stimulants on yield and quality of grain corn grown in Piedmont subprovince of Dagestan

Abstract: Field experiments were carried out on chestnut soils of Piedmont Dagestan in 2018-2020. Hybrids of grain corn treated with different growth stimulants were the object of еру research. The experiments showed that the harvesting ripeness of hybrids ROSS 299 MV and Mashuk 355 MV occurred 2...5 days earlier after treatment with growth stimulants compared to the control. The growth stimulants used in the experiment did not have a significant effect on seed germination rate. Among the studied hybrids, the highest se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…At the same time, the saprophytic and pathogenic microflora of the seeds is suppressed, their germination energy increases, root formation, growth and the development of plants increase, and resistance to diseases during the growing season increases. The crop yield increases up to 30% in comparison with the control [ 36 , 37 , 38 ]. However, quite commonly used crop regulators and growth promoters are toxic and detrimental to the environment, as well as having a negative impact on human health.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the saprophytic and pathogenic microflora of the seeds is suppressed, their germination energy increases, root formation, growth and the development of plants increase, and resistance to diseases during the growing season increases. The crop yield increases up to 30% in comparison with the control [ 36 , 37 , 38 ]. However, quite commonly used crop regulators and growth promoters are toxic and detrimental to the environment, as well as having a negative impact on human health.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, there is a sufficient selection of corn varieties and hybrids for growing for green mass and grain [9][10]. For the conditions of Siberia, it is important to use early ripening hybrids of the intensive type, which have high productivity in combination with a balanced amino acid composition of proteins [11][12]. It has been shown that elements of production technology affect the quality of corn grain by increasing the concentration of essential amino acids in proteins [13][14].…”
Section: Introductionmentioning
confidence: 99%